Application of articaine in endoscopic endonasal dacryocystorhinostomy: a retrospective study - Liu, Shulin; Shui, Li; Liu, Zhaohui; Li, Qi (Frontiers in Medicine, 2024)
Background To investigate the comparative effects of local anesthesia using lidocaine with adrenaline vs. articaine with adrenaline in endoscopic endonasal dacryocystorhinostomy (EN-DCR). Methods This retrospective study included a total of 180 patients. These patients were categorized into two groups: the lidocaine group, which received 2% lidocaine (1:100,000 adrenaline), and the articaine group, which received 4% articaine (1:100,000 adrenaline) for local anesthesia. The study compared anesthesia efficacy, intraoperative pain levels, intraoperative bleeding, as well as differences in heart rate and blood pressure between the two groups. Results The articaine group demonstrated a significantly lower visual analog scale (VAS) pain score when compared to the lidocaine group, measuring at 4.4 ± 0.6 cm vs. 5.0 ± 1.0 cm, respectively (P < 0.0001). Additionally, the articaine group exhibited a higher anesthesia efficacy compared to the lidocaine group (89.0% vs. 76.6%, p = 0.0487). Notably, the articaine group experienced less nasal mucosal bleeding during the surgery in contrast to the lidocaine group (p = 0.004). However, there were no statistically significant differences in changes in blood pressure and heart rate between the two groups (p > 0.05). Conclusion This study demonstrated that 4% articaine (1:100,000 adrenaline) has superior clinical effectiveness in comparison to 2% lidocaine (1:100,000 adrenaline) in EN-DCR.